THU0468 Up-Regulation of Mir-21 in Peripheral Blood Mononuclear Cells of Early Onset Psoriatic Arthritis: Changes from Baseline after Appropriate Therapy. (10th June 2014) - Ciancio, G.; Ferracin, M.; Zagatti, B.; Saccenti, E.; Ilaria, F.; Bagnari, V.; Trotta, F.; Negrini, M.; Govoni, M.
Abstract : Background: Micro-RNAs (miRNAs) are small non-coding RNAs that negatively regulate gene expression.It is known that an altered miRNA expression plays an important role in cancer.A new emerging role for miRNAs has been evidenced in the pathogenesis of rheumatic diseases such as rheumatoid arthritis and psoriasis.Recently, we evaluated miRNA expression in peripheral blood mononuclear cells (PBMCs) of 21 patients with psoriatic arthritis (PsA) of recent onset and naïve from treatment by miRNA microarray. Three mi-RNAs (miR-21-5p, miR-34a and miR-21-3p) resulted significantly upregulated compared to 12 healthy controls. Objectives: We set out to validate microarray results in the same series of PsA patients and controls;and to check for changes in the mi-RNA expression from baseline after appropriate therapy. Methods: We performed a quantitative RT-PCR (RT-qPCR) analysis for miR-21 in the entire series of 21 PsA patients and 12 controls. We also checked for changes in miR-21 expression profile from baseline after 3 months of appropriate therapy (symptomatic therapy, DMARDs, TNF-alpha blockers) in 9 of the 21 PsA patients. Mature miRNA expression was evaluated by Taqman miRNA assays (Applied Biosystem) specific for miR-21 and RNU6B as reference gene, according to the manufacturer's protocol. Five ng of total RNA was reverse transcribed using the specific looped primer; quantitative PCR was conducted using the standard Taqman MiRNA assay. Each sample was analyzed in triplicate.The amount of target, normalized on U6 RNA amount, was calculated using 2-ΔCt (Comparative Ct) method. Significance in RT-qPCR results was determined by unpaired t test with Welch's correction and graphs were created using GraphPad software Results: In comparison with healthy controls, the up-regulation of miR-21 in PsA was validated and confirmed by RT-qPCR (p<0.05). In the treated PsA patients, miR-21 resulted significantly reduced (p<0.05) after 3 months of therapy compared to baseline Conclusions: The upregulation of miR-21 in early, active and naïve of treatment PsA was confirmed and validated. Compared to baseline, miR-21 resulted significantly reduced after 3 months of appropriate therapy. These results, if confirmed on a larger number of patients, could have two important implications. First, it calls into question all the previous studied on miRNA performed on PBMC of pharmacologically treated patients. Second, it opens new horizons not only in understanding pathogenic mechanisms of the disease but also in identifying useful diagnostic and prognostic biomarkers and new possible therapeutic targets in PsA. For the latter purpose, comparative studies with other chronic inflammatory conditions other than PsA are needed References: Ciancio G, Ferracin E, Zagatti B, et al. Microrna Expression Profiles in Peripheral Blood Mononuclear Cells of Early Onset Psoriatic Arthritis. Arthritis Rheumatism, 2012, 64(10 Suppl):433. Alevizos I, Illei GG: MicroRNAs as biomarkers in rheumatic diseases. Nat Rev Rheumatol 2010, 6:391-398 Acknowledgements: The authors gratefully acknowledge the support of the Regione Emilia Romagna and the University of Ferrara which made this study possible. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4448